2019
DOI: 10.1212/wnl.0000000000007096
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter comparison of MOG-IgG cell-based assays

Abstract: Objectives To compares 3 different myelin oligodendrocyte glycoprotein–immunoglobulin G (IgG) cell-based assays (CBAs) from 3 international centers. Methods Serum samples from 394 patients were as follows: acute disseminated encephalomyelitis (28), seronegative neuromyelitis optica (27), optic neuritis (21 single, 2 relapsing), and longitudinally extensive (10 single, 3 recurrent). The control samples were from patients with multiple sclerosis (244), hypergammaglobuline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
175
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 10 publications
7
175
0
2
Order By: Relevance
“…Overall, the median age of the patients at disease onset was 28 years, and the median disease duration at serum sampling was 11.5 years. Only 2 patients (0.03%) had MOG antibodies, consistent with the antibody specificity reported in previous studies, 9,10 although the current study included different subtypes of MS. Besides noting the high specificity of the methods used, the authors conclude that in clinical practice, patients fulfilling the 2010 McDonald criteria of MS (with typical features) do not need MOG antibody testing.…”
supporting
confidence: 91%
“…Overall, the median age of the patients at disease onset was 28 years, and the median disease duration at serum sampling was 11.5 years. Only 2 patients (0.03%) had MOG antibodies, consistent with the antibody specificity reported in previous studies, 9,10 although the current study included different subtypes of MS. Besides noting the high specificity of the methods used, the authors conclude that in clinical practice, patients fulfilling the 2010 McDonald criteria of MS (with typical features) do not need MOG antibody testing.…”
supporting
confidence: 91%
“…A recent large study of MOG antibodies in MS showed it is detected in only 0.2%, highlighting its utility in discriminating from MS [8]. While in our study we used two sites for MOG-IgG detection, our multi-center collaborative studies have shown the live-cell based MOG assay cut-offs show consistent results across centers for a non-MS phenotype [77]. The frequency of MOG-IgG and AQP4-IgG coexistence was reported at 0.06% which suggests a distinct immunopathogenesis to MOGAD and AQP4-IgG seropositive NMOSD, rather than MOG-IgG representing an epiphenomenon [37].…”
Section: Discussionmentioning
confidence: 67%
“…Recently, a commercial CBA for MOG-Abs detection relying on fixed cells has become available. In a three-center comparison, the fixed CBA showed rather good concordance with the live CBAs, with slightly lower specificity (30).…”
Section: Background Of the Assaymentioning
confidence: 89%